The extension of clusters: Differences-in-difference evidence from the Bavarian state-wide cluster policy - Oliver Falck; Stephan Heblich; Stefan Kipar (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2008)
If one cluster increases local competitiveness, can politicians, by interlinking clusters, achieve an even better effect at the state level? To answer this question, the paper analyzes the Cluster Initiative introduced in 1999 by the Bavarian State Government. The purpose of the initiative was to create a Bavarian-wide innovation network in support of state-wide knowledge flows. Using a difference-in-differences approach, we find that introducing the Bavarian-wide cluster policy increased the likelihood of innovation by a firm in the targeted industry by 4 to 7 percentage points. However, this effect is mainly driven by large firms' increased likelihood to innovate.
Keywords: R38; R11; O32; 330; Difference-in difference; cluster policy; regional policy; Regionalpolitik; Innovationspolitik; Business Network; Regionale Konzentration; Wirtschaftspolitische Wirkungsanalyse; Innovation; Bayern